Towards a dynamic model of terrorist radicalization - Clara Volintiru (European Institute of Romania, 2010)
This paper attempts to develop a theoretical assessment of how radicalization is reached. For this purpose, a Dynamic Model is proposed that accounts for the interaction between an individual's motivations and the determining factors of the surrounding context. It is a process-tracing analysis that emphasizes the specific elements of each phase of the process. This sequential understanding of both individual and aggregate (societal) radicalization is extremely useful in developing adapted, efficient counter-measures. The Dynamic Model of Radicalization is applied to the case studies of Chechnya and Kosovo and shows how, once established the overall causal mechanism that leads to radicalization in each case, we can observe more clearly the specific intervening factors that have lead to ultimately different outcomes. The proper understanding of the dynamics of radicalization is essential for developing effective policies to tackle with such issues as securing the EU border areas, and combating terrorism both at home, and abroad.
Keywords: 330; Radicalization; Terrorism; Kosovo; Chechnya; Radikalismus; Terrorismus; Dynamische Wirtschaftstheorie; Tschetschenien; Kosovo